2009
DOI: 10.1007/s00405-009-0951-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of laryngeal tumors and tumoral extension by multislice computed tomography-virtual laryngoscopy (MSCT-VL)

Abstract: Virtual endoscopy is becoming a widely used non-invasive clinical diagnostic tool. The present study was designed to compare the sensitivity and specificity of the conventional endoscopy and virtual laryngoscopy with respect to laryngeal masses. A total of 38 patients (20 males, 18 females, mean age 61 years) with the complaint of hoarseness were included in the study. Laryngeal mucosa, lumen and mass pathology were evaluated initially by direct endoscopy and then by virtual laryngoscopy during multislice CT o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…We obtained from their combination a final 95% CI 0.51-0.88 for Se and a value of 95% CI 0.55-0.96 for Sp, reporting a very high I 2 value for both Se (87.7%) and Sp (95.91%), where the lowest rates of Se were reported by Hartl et al (220) and Allegra and colleagues (218), whilst Gordin and Beser (191,222) showed the lowest rate for Sp. Here the hypothesis of hegemony among these different studies was not statistically significant ( Figure 16).…”
mentioning
confidence: 88%
“…We obtained from their combination a final 95% CI 0.51-0.88 for Se and a value of 95% CI 0.55-0.96 for Sp, reporting a very high I 2 value for both Se (87.7%) and Sp (95.91%), where the lowest rates of Se were reported by Hartl et al (220) and Allegra and colleagues (218), whilst Gordin and Beser (191,222) showed the lowest rate for Sp. Here the hypothesis of hegemony among these different studies was not statistically significant ( Figure 16).…”
mentioning
confidence: 88%
“…The European Laryngeal Society (ELS) 4,5 included this type of evaluation in a basic voice assessment protocol. This protocol included endoscopy 6–8 and acoustic, auditory-perceptual and aerodynamic evaluations 918 after voice therapy or phonosurgical treatments 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Virtual endoscopy has the added advantage that it can also be used for educational purposes, as an excellent research tool for understanding and teaching normal and abnormal pathology and in surgical planning, all without the need for additional radiation exposure or discomfort to the patient [20,24] provided staging CT images have already been undertaken.…”
Section: Discussionmentioning
confidence: 99%